Evaluation of support and training sign language services at Setotolwane Secondary School - Chake, Nkhululeko (University of Limpopo, 2018)
Support and training services serves as a key to easy life for the deaf community. The whole experience allows deaf people to batter people who understand who they are and how life should be. The purpose of this study was to evaluate the support and training Sign Language services provided at Setotolwane Secondary School. Data was collected from Setotolwane Secondary School using semi-structured interviews. Qualitative approach was used where ten (10) people were interviewed. Among then there were five (5) deaf learners and five (5) Sign Language teachers. Finally, the results show that deaf people are being provided with support and training Sign Language service. The services provided are not enough that are further recommendations to improve in the situation. This study aims to indicate how relevant support and training can improve and empower the deaf community around the world. Keywords Sign Language, support services, training services
Thesis (M. A.. (African Languages)) -- University of Limpopo, 2018
Keywords: Sign language; Support services; training services; Sign language; Deaf - Services for; Interpreters for the deaf